Indicators of the effectiveness of school theater in inculcating values in Algeria: 15 interviews with teachers from the city of Constantine - Benarioua, Amel (Journal of Human Sciences, 2022)
This study came to reveal the indicators that ensure the efficacy of extracurricular activities in educational institutions and their role in instilling social values in Algerian society, based on 15 interviews with teachers who have 10 years experience in primary education, where the interactive and survival areas of the school theater activity become clear in controlling and consolidating values among students, if there are indicators of building purposeful educational activity in primary education . Islamic values and their consolidation depends on raising the level of educational activities in schools and the practice of school theater represents the most important tributary in achieving educational goals related to national, social and human values .